II Pillar Pension Funds: How the Selection of Fund Influences the Size of the Old-age Pension - Rabikauskaitė, Viktorija; Novickytė Lina (Ekonomika, 2015)
The government, in order to achieve the welfare of the citizens in the retirement age to keep pace with the working people, carried out the various pension systems transformations. The working people’s welfare is growing due to the economic progress, so there is a theory of economics, which examines the existing income redistribution in time. It should be noted that in order to ensure the financial well-being in old age it is necessary to efficiently allocate the scarce resources. In Lithuania, the existing three pillar pension system allows each employee to contribute to their own financial well-being in the future. This article aims to assess the second pillar pension fund performance and how fund differences affect the amount of old age pension. The analysis made it possible to determine the correlation between the return generated by the fund and the number of participants in the fund; the spreadsheet is provided, which allows estimating the influence of the choice of different funds on the size of the retirement pension. It was found that fund return and the number of participants in the fund have a negative correlation. This shows that the part of households who raise money in fund with the lowest return will be much poorer, and the corresponding result is a smaller pension. It may be noted that the accumulation of different pension fund reserves have a significant impact on the future pension size (this difference can be as high as 230%).